Polarized radio emission unveils the structure of the pre-supernova circumstellar magnetic field and the radio emission in SN1987A. Issue 4 (6th December 2022) - Petruk, O; Beshley, V; Orlando, S; Bocchino, F; Miceli, M; Nagataki, S; Ono, M; Loru, S; Pellizzoni, A; Egron, E
ABSTRACT: The detected polarized radio emission from the remnant of SN1987A opens the possibility to unveil the structure of the pre-supernova (pre-SN) magnetic field (MF) in the circumstellar medium. Properties derived from direct measurements would be of importance for understanding the progenitor stars and their MFs. As the first step to this goal, we adopted the hydrodynamic (HD) data from an elaborated three-dimensional (3D) numerical model of SN1987A. We have developed an approximate method for 'reconstruction' of 3D MF structure inside SN remnant on the 'HD background'. This method uses the distribution of the MF around the progenitor as the initial condition. With such a 3D magnetohydrodynamic model, we have synthesized the polarization maps for a number of SN1987A models and compared them to the observations. In this way, we have tested different initial configurations of the MF as well as a structure of the synchrotron emission in SN987A. We have recovered the observed polarization pattern and we have found that the radial component of the ambient pre-SN MF should be dominant on the length-scale of the present-day radius of SN1987A. The physical reasons for such a field are discussed.